Physiotherapy with manual lymphatic drainage in post-mastectomy lymphedema (Research, Society and Development, 2025)
Upper-limb lymphedema is one of the most prevalent complications after mastectomy and is directly associated with axillary lymph node removal and radiotherapy, resulting in interstitial protein accumulation, pain, functional limitation, and impaired quality of life. Manual lymphatic drainage (MLD) is one of the main physiotherapeutic resources used to reduce edema, stimulate lymphatic return, and improve functionality. Objective: To discuss the role of physiotherapy using manual lymphatic drainage in the treatment of post-mastectomy lymphedema, highlighting the benefits and effectiveness of this technique. Methods: This is an integrative literature review. Searches were performed in Google Scholar, PubMed, and SciELO using descriptors related to manual lymphatic drainage and post-mastectomy lymphedema. Articles published in the last five years were included, screened by title and abstract, selecting only studies in which MLD was the main intervention. After applying inclusion and exclusion criteria, seven articles comprised the final sample. Results: A total of 124 studies were initially identified across the platforms, which were reduced after applying time and relevance criteria. The analysis of titles, abstracts, and full texts resulted in a final sample of seven studies. Conclusion: Manual lymphatic drainage is an effective and safe resource for the treatment of post-mastectomy lymphedema, especially when integrated into comprehensive physiotherapy programs. Despite favorable results, standardized clinical trials are needed regarding the technique, frequency, and intensity of interventions.